Effects of a magnetic field on the optoelectronic properties of mono- and bi-layer transition metal dichalcogenides. (14th June 2018) - Mlinar, Vladan
Abstract: We report a theoretical study on the effects of an external magnetic field on the electronic and optical properties of mono- and bi-layer MoS2, and bilayer MoS2 /WS2 heterostructures. The direction of an applied magnetic field determines (i) the strength of the coupling between the atomic orbital moments of the structure and the field, and (ii) Zeeman contribution to the splitting of the VB and CB levels with the amplitude of the applied field. Whereas for a magnetic field applied perpendicular to the structure, calculated real part of optical conductivity reveals optical transitions red-shifted compared to zero magnetic field case, conductivity is unaffected by the the amplitude of an in-plane applied magnetic field. We show that through modifying atomic d-orbitals conduction and valence band states by an applied electric field, we can determine and control the impact of a magnetic field on the optical response of these materials. We employ our parametrized tight-binding model with non-orthogonal sp 3 d 5 orbitals and spin–orbit coupling, which was advanced to include the effects of an external magnetic field through Peierls substitution in the wave vector and the Zeeman energy term.